IMPLIKASI LITERASI MEDIA DALAM MENGUBAH PERILAKU MASYARAKAT KOTA PONTIANAK TERHADAP KABAR BOHONG - Dewi Utami (Commed : Jurnal Komunikasi dan Media, 2019)
Whether consciously or not, social media users are active spreaders of fake/false news. Those who have an understanding of media literacy should be able to overcome the spread of fake/false news. This study intended to examine how media literacy values acquired beforehand by individuals can compete with stimulus in the form of potentially fake/false news before it is finally decided to be disseminated or not. This research rests on the principles of social judgment theory and uses in-depth interviews to collect data. The result shows that there is an attitude of restraint when the characteristics of fake/false news on a message are successfully marked. In addition, the mismatch of value references possessed by individuals with ideas offered by fake/false news lead to 3 types of behavior: muting, compromising, or actively rejecting.